2002
DOI: 10.1046/j.1463-6395.2002.00066.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the spermatozoa of the Microhylidae (Anura, Amphibia)

Abstract: Microhylid spermatozoa show the autapomorphic condition of possessing a thin post‐mitochondrial cytoplasmic collar. Their spermatozoa are apomorphic in several respects. They have lost the distinct nuclear shoulder, endonuclear canal and axial perforatorium observed in urodeles, caecilians and primitive frogs, possess a conical perforatorium and apomorphically lack any fibres associated with the axoneme. The spermatozoa of Cophixalus, however, differ in several respects from those of the other microhylids exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…Kwon and Lee () suggested that the presence of a simple axoneme, with no undulating membrane, was a derived trait in the genera Rana , Rhacophorus , and Xenopus . Meyer et al () also concluded that the tail of the spermatozoa of Litoria had undergone a similar process of simplification, and Scheltinga et al () identified a similar process in the microhylids Cophixalus , Calluella , Ctenophryne , and Sphenophryne . Aguiar‐Junior et al () also identified the thickening of the undulating membrane and the absence of a juxta‐axonemal fiber as an apomorphy in Ameerega trivittatus and A. hahneli (described as Epipedobates trivittatus and E. hahnelii , respectively).…”
Section: Discussionmentioning
confidence: 98%
“…Kwon and Lee () suggested that the presence of a simple axoneme, with no undulating membrane, was a derived trait in the genera Rana , Rhacophorus , and Xenopus . Meyer et al () also concluded that the tail of the spermatozoa of Litoria had undergone a similar process of simplification, and Scheltinga et al () identified a similar process in the microhylids Cophixalus , Calluella , Ctenophryne , and Sphenophryne . Aguiar‐Junior et al () also identified the thickening of the undulating membrane and the absence of a juxta‐axonemal fiber as an apomorphy in Ameerega trivittatus and A. hahneli (described as Epipedobates trivittatus and E. hahnelii , respectively).…”
Section: Discussionmentioning
confidence: 98%
“…O filamento caudal apresenta um axonema típico (9+2) sem nenhum anexo caudal em R. pipiens (Screber, 1782) e R. clamitans (Latreille, 1801) (POIRIER & SPINK, 1971) e alguns Microhilídeos (SCHELTINGA et al, 2002), ou com dois axonemas em Megophrys montana (Kuhl & van Hasselt, 1822) (ASA & PHILLIPS, 1988) e Lepdobatrachus laevis (Budgett, 1899) (WAGGENER & CARROL JR., 1998). O filamento caudal com axonema, membrana ondulante e bastão axial está presente em Pachymedusa dacnicolor (RASTOGI et al, 1988) e Bufo gargarizans Cantor, 1842(KWON & LEE, 1995.…”
Section: Discussionunclassified
“…A grande variação morfológica e morfométrica na estrutura do acrossomo, perfuratorium e filamento caudal tem contribuído também para a caracterização taxonômica e filogenética (FOUQUETTE & DELAHOUSSAYE, 1977;GARRIDO et al, 1989;LEE & JAMIESON, 1992JAMIESON et al, 1993;KWON & LEE, 1995;MEYER et al, 1997;SCHELTINGA et al, 2002).…”
unclassified
“…Despite numerous studies that point towards its deficiencies (e.g. Kluge and Farris, 1969;Lynch, 1973;Sokol, 1975Sokol, , 1977Duellman and Trueb, 1986;Ruvinsky and Maxson, 1996;Maglia, 1998;Emerson et al, 2000;Maglia et al, 2001;Scheltinga et al, 2002;Haas, 2003;Roelants and Bossuyt, 2005;San Mauro et al, 2005;Van der Meijden et al, 2005), the current classification continues in many of its parts to reflect sociological conservatism and the traditional preoccupation with groupings by subjective impressions of overall similarity; special pleading for characters considered to be of transcendent importance; and notions of ''primitive'', ''transitional'', and ''advanced'' groups instead of evolutionary propinquity. Understanding of frog relationships remains largely a tapestry of conflicting opinion, isolated lines of evidence, unsubstantiated assertion, and unresolved paraphyly and polyphyly.…”
Section: Anuramentioning
confidence: 99%
“…Lynch (1973), Estes (1981), Trueb (1986), Milner (1988), Nussbaum and Wilkinson (1989), Trueb and Cloutier (1991), Ford and Cannatella (1993), Larson and Dimmick (1993), Milner (1993, McGowan and Evans (1995), Shubin and Jenkins (1995), M. Wilkinson and Nussbaum (1996), Laurin and Reisz (1997), Laurin (1998a), Maglia (1998), Carroll et al (1999, M. Nussbaum (1999), Carroll (2000a), Laurin et al (2000), Milner (2000), J.S. Anderson (2001), Gardner (2001), Kaplan (2001), Zardoya and Meyer (2001), Gardner (2002), , Laurin (2002), Scheltinga et al (2002), andBáez andPugener (2003). What we found, not surprisingly, is that different studies tended to generalize across different exemplars, even if they were working on the same groups, and that in some cases putative synapomorphies had been so reified through repetition in the literature that it was difficult, if not impossible, to ascertain which taxa (much less which specimens) had actually been evaluated for which characters.…”
Section: A Taxonomy Of Living Amphibiansmentioning
confidence: 99%